Native vs. non-native EFL teachers: Who are better? - Kurniawati Kurniawati; Dini Rizki (Studies in English Language and Education, 2018)
This paper discusses possible advantages of having Non-Native English-Speaking Teachers (NNESTs) to teach English as a Foreign-Language (EFL) especially in Asian countries when they are often regarded as inferior to their Native English-Speaking Teachers (NESTs) counterparts. A native speaker fallacy has emphasized that NESTs are better teachers of EFL and have put NNESTs at a disadvantage. Actually, NNESTs possess advantages that can make them better teachers for teaching English in an EFL/ESL setting connected with their own EFL learning experiences and with sharing the same first language and cultural background with their students. While considered to have lower English language proficiency and lower self-confidence compared to NESTs, NNESTs who have made the effort to become quality teachers can position themselves as ideal English teachers in their own environment.